Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cancers13174284
|View full text |Cite
|
Sign up to set email alerts
|

TP53 in Biology and Treatment of Osteosarcoma

Abstract: The TP53 gene is mutated in 50% of human tumors. Oncogenic functions of mutant TP53 maintain tumor cell proliferation and tumor growth also in osteosarcomas. We collected data on TP53 mutations in patients to indicate which are more common and describe their role in in vitro and animal models. We also describe animal models with TP53 dysfunction, which provide a good platform for testing the potential therapeutic approaches. Finally, we have indicated a whole range of pharmacological compounds that modulate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 209 publications
0
28
0
Order By: Relevance
“…Expression of mutated p53 has been associated with poor prognosis and response to chemotherapy in many human malignancies ( 20 , 21 ). p53 mutations are also frequently detected in OS and have been suggested as possible targets of novel therapies ( 22 ). p53 has been also found to be overexpressed in a significant subset of OS of the jaws ( 9 , 16 , 23 , 24 ) Specifically, p53 positivity was detected in 88% and 52% of the jaw OS cases reported by Lopes et al .…”
Section: Discussionmentioning
confidence: 99%
“…Expression of mutated p53 has been associated with poor prognosis and response to chemotherapy in many human malignancies ( 20 , 21 ). p53 mutations are also frequently detected in OS and have been suggested as possible targets of novel therapies ( 22 ). p53 has been also found to be overexpressed in a significant subset of OS of the jaws ( 9 , 16 , 23 , 24 ) Specifically, p53 positivity was detected in 88% and 52% of the jaw OS cases reported by Lopes et al .…”
Section: Discussionmentioning
confidence: 99%
“…The change further emphasized that the assessment of bone tumors should be more thorough and personalized. We reviewed previous studies on prognostic-related molecular markers and found that the vascular endothelial growth factor (VEGF) and p53 mutation were two important biomarkers related to the evaluation of the biological aggressiveness of osteosarcoma and GCTB (3,(8)(9)(10)(11)(12)(13)(14)(15). Angiogenesis occurs in numerous biological processes, which is essential for the growth of tumors and metastases.…”
Section: Introductionmentioning
confidence: 99%
“…It can be activated through various stresses, including DNA damage, oncogene expression, hypoxia, and replication stress, as well as cellular metabolic changes. Once activated, p53 can trigger apoptosis, cell cycle arrest, or senescence to suppress tumor progression by activating its target genes [15,16]. CDKN1A is the critical induced gene in p53-mediated cellular senescence.…”
Section: Introductionmentioning
confidence: 99%